Pengaruh Pertumbuhan Penjualan, Leverage Operasi, Dan Struktur Aktiva Terhadap Struktur Modal - Novianti, Lely; Budyastuti, Triyani (Universitas Gorontalo, 2022)
The purpose of the research is to analyze the influence sales growth, operating leverage, and asset tangibility of the capital structur. The method used in this study is purposive sampling. The population in this study is the mining sector companies listed on the Stock Exchange as many as 47 companies. The number of samples studied in this study was as much as 132 samples. The collection of data used in this study of secondary data came from the 33 financial statements of the mining company in the period 2017-2020. Analysis of data from this study uses multiple linear regression. Based on the results of the study concluded that sales growth and operating leverage has no influence on the capital structure, while the asset tangibility has influence on the capital structure.